Theories of gender and power differences: A discussion - Jariah Mohd. Jan (Journal of Modern Languages)
Early studies on gender differences in conversation focused on differences between male and female conversational styles. For nearly all of these issues of stylistic and conversational differences, there are many some contradictory findings, and it seems that one must look closely at the nature of the circumstances in order to predict how men and women will behave verbally. This paper discusses the theories of gender and power differences namely deficit, dominance and sub-cultural as proposed by researchers in the field of language and gender. Most recent research into gender and language challenges the dominant sex-difference oriented approaches. which maintain that women are different from men, whether essentially or by socialisation (e.g., Coales, 1986). This sex-difference view either condemns women's different speech as socially dysfunc- tional and deficient (e.g., Lakoff, 1975), or embraces it as a 'different but equally valid' culture (e.g., Tannen, 1990). the 'different and deficient' approach is criticised for implying that, to improve their social status, individual women should transform their style, and adjust themselves to men's linguistic nouns. Nevertheless, in principle, it is clear that in many circumstances, women and men have access to the same set of linguistic and conversational devices, and tend to use them differently but for the same purposes. Apparent differences in usage reflect differences in status and in goals.